2012
DOI: 10.1155/2012/106783
|View full text |Cite
|
Sign up to set email alerts
|

A Novel System for Rapid and Cost-Effective Production of Detection and Diagnostic Reagents of West Nile Virus in Plants

Abstract: The threat of West Nile virus (WNV) epidemics necessitates the development of a technology platform that can produce reagents to support detection and diagnosis rapidly and inexpensively. A plant expression system is attractive for protein production due to its low-cost and high-scalability nature and its ability to make appropriate posttranslational modifications. Here, we investigated the feasibility of using plants to produce two WNV detection and diagnostic reagents to address the current cost and scalabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…For N. benthamiana leaves that were entirely infiltrated with Agrobacteria containing geminiviral vectors, GFP expression was observed over the entire leaf area under UV light starting from as early as 2 dpi and reached peak accumulation at 4 dpi ( Figure 4C). This early GFP expression by geminiviral vector is consistent with previous results of other recombinant proteins 14,16,18,19 . In contrast, leaves infiltrated with MagnICON vector-containing Agrobacterium combinations showed GFP fluorescence only after 5 dpi and reached its maximum accumulation at 7 dpi (Figure 4D).…”
Section: Expression Of Fluorescent Proteins By Syringe Infiltrationsupporting
confidence: 91%
See 2 more Smart Citations
“…For N. benthamiana leaves that were entirely infiltrated with Agrobacteria containing geminiviral vectors, GFP expression was observed over the entire leaf area under UV light starting from as early as 2 dpi and reached peak accumulation at 4 dpi ( Figure 4C). This early GFP expression by geminiviral vector is consistent with previous results of other recombinant proteins 14,16,18,19 . In contrast, leaves infiltrated with MagnICON vector-containing Agrobacterium combinations showed GFP fluorescence only after 5 dpi and reached its maximum accumulation at 7 dpi (Figure 4D).…”
Section: Expression Of Fluorescent Proteins By Syringe Infiltrationsupporting
confidence: 91%
“…No green fluorescence was observed from leaves infiltrated with negative control Agrobacterium mixtures of pREP110 + p19 (Figure 4B) or pICH15879 + pCH14011 (data not shown), indicating that the fluorescence was specific to the GFP gene and was not the result of background fluorescence from the leaves. At its peak accumulation, the fluorescence of MagnICON vector-expressed GFP is more intense than that of geminiviral vector ( Figure 4C and 4D), similar to results previously obtained for other recombinant proteins 8,18 . The temporal expression pattern and the relative fluorescent intensity of DsRed are similar to that of GFP (data not shown).…”
Section: Expression Of Fluorescent Proteins By Syringe Infiltrationsupporting
confidence: 86%
See 1 more Smart Citation
“…Finally, this system integrates the posttranslational processing capacity of eukaryotic plant cells, for producing complex proteins. Along with others, our laboratory has expressed numerous proteins from small subunit vaccines to large immune complexes, with this system [5,6,28,29]. The collective results the delivered DNA [3].…”
Section: Vector Constructionmentioning
confidence: 99%
“…The collective results the delivered DNA [3]. The ability to deliver vectors to a majority of the have demonstrated that this system is robust and drives high levels of target protein accumulation up to 1 mg per gram of leaf fresh weight (LFW), within 7 to 10 days after agroinfiltration [5,6,24,28,29]. This system retains the speed and expression amplification of viral vectors, while gaining the flexibility of nuclear gene expression.…”
Section: Vector Constructionmentioning
confidence: 99%